2002
DOI: 10.1002/cncr.10822
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of multiple recurrences of superficial (Ta/T1) transitional cell carcinoma of bladder and effects of clinicopathologic and biochemical factors

Abstract: BACKGROUND Although multiple sequential recurrences are one of the most important characteristics of superficial transitional cell carcinoma (TCC) of the bladder, few studies have examined multiple sequential recurrence patterns and the clinicopathologic and biochemical factors associated with these patterns. METHODS Two hundred seventy superficial TCC bladder carcinoma patients were followed. Clinical, pathologic, and tumor marker (p53, MIB‐1, bcl‐2, c‐erb B‐2, and epidermal growth factor receptor) data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Santos et al [35] have shown that MIB-1-positive tumors have a worse course of disease. Yan et al [47] observed that MIB-1 could be used to identify patients with high risk for recurrence. Helpap and Köllermann [10] have shown that pattern and intensity of staining for MIB-1 and 34βE12 might help to distinguish grades.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Santos et al [35] have shown that MIB-1-positive tumors have a worse course of disease. Yan et al [47] observed that MIB-1 could be used to identify patients with high risk for recurrence. Helpap and Köllermann [10] have shown that pattern and intensity of staining for MIB-1 and 34βE12 might help to distinguish grades.…”
Section: Discussionmentioning
confidence: 98%
“…p63 staining was considered positive if nuclear percentage between 0 (stained cells <10%), 1 (>10% stained cells <80%) and 2 (stained cells >80-100%) was assessed. Regarding p53, tumors with nuclear immunoreactivity of more than 10% were considered positive according to other pervious studies [26,27,47].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The grade distribution for patients with T0 and T1 disease was 29%, 52.6%, and 18.4% for WHO Grades 1, 2, and 3, respectively, based on weighted means derived from 6 articles involving 4514 patients. [13][14][15][16][17][18] In patients with T2 disease and higher, 90% of patients had high-grade disease. 11 Cancer recurrence and progression rates depend heavily on the stage of disease.…”
Section: Assumptionsmentioning
confidence: 99%
“…Su valor como factor predictivo en el cáncer vesical está todavía también por determinar. Los estudios recientes mayoritariamente consideran que la expresión inmunohistoquímica de esta proteína no presenta un valor significativo ni en el análisis univariante ni en el multivariante 1, [30][31][32][33][34] . En tumores pT1G3, Wolf HK y cols.…”
Section: Inmunohistoquímica De Bcl-2unclassified